Effects of plasmapheresis frequency on health status and exercise performance in men: A randomized controlled trial - Mortier, Alexandre; Khoudary, Jina; Dooslaer de Ten Ryen, Sophie; Lannoy, Camille; Benoit, Nicolas; Antoine, Nancy; Copine, Sylvie; Van Remoortel, Hans; Vandekerckhove, Philippe; Compernolle, Veerle; Deldicque, Louise (Vox sanguinis, 2024)
Background and Objectives Most research studies on the effects of repeated plasma donation are observational with different study limitations, resulting in high uncertainty on the link between repeated plasma donation and health consequences. Here, we prospectively investigated the safety of intensive or less intensive plasma donation protocols. Materials and Methods Sixty‐three male subjects participated in this randomized controlled trial and were divided into low‐frequency (LF, once/month, n = 16), high‐frequency (HF, three times/month, n = 16), very high‐frequency (VHF, two times/week, n = 16) and a placebo (P, once/month, n = 15) groups. Biochemical, haematological, clinical, physiological and exercise‐related data were collected before (D0), after 1½ months (D42) and after 3 months (D84) of donation. Results In VHF, red blood cells, haemoglobin and haematocrit levels decreased while reticulocyte levels increased from D0 to D84. In both HF and VHF, plasma ferritin levels were lower at D42 and D84 compared to D0. In VHF, plasma levels of albumin, immunoglobulin G (IgG), immunoglobulin A (IgA) and immunoglobulin M (IgM) dropped from D0 to D42 and remained lower at D84 than at D0. In HF, plasma IgG, IgA and IgM were lower at D42, and IgG and IgM were lower at D84, compared to D0. Few adverse events were reported in HF and VHF. Repeated plasma donation had no effect on blood pressure, body composition or exercise performance. Conclusion VHF plasmapheresis may result in a large reduction in ferritin and IgG levels. HF and VHF plasmapheresis may result in little to no difference in other biochemical, haematological, clinical, physiological and exercise‐related parameters.